Black Theology of Liberation (Is it the) Thing of the Past? A Theological Reflection on Black Students' Experiences - Kobe, Lerato (Missionalia, 2018)
This article pursues a theological reflection on black students' experiences using the liberative paradigm found in Black theology of liberation (BTL). Reflecting on black students' experiences in the classroom, the article asks the question; is Black theology of liberation the thing of the past? Pertaining to the question, the article links James Cone and Steve Biko's experiences in university with my own experiences in the university, particularly as a student of theology in South Africa. Therefore, the focus of the article is threefold; James Cone's experiences as a student of theology in America, Steve Biko's experiences as a black student under the apartheid government. Lastly, the article investigates my own experiences to present a theological reflection on black students' experiences post-apartheid